Dynamic safe regions for moving range queries in mobile navigation. (23rd September 2014) - Al–Khalidi, Haidar; Taniar, David; Betts, John; Alamri, Sultan
The cost of monitoring and updating the location of Moving Queries is very high, as the calculation of a range query needs to be re–evaluated whenever the query moves. Previous efforts to reduce this cost have proposed reducing the frequency of communication between query and server. However, because all possible objects continue to be surveyed using these approaches, substantial cost reduction is not possible. This paper introduces two novel techniques: the continuous basic safe region, by calculating the closest objects to the border of the moving query, and the continuous extended safe region, by calculating the intersections among several range objects. Inside these safe regions there is no need to update the query as the set of objects of interest does not change. We compare the size of the safe regions obtained using these two methods and show their potential to greatly reduce computations and communications cost in client–server architectures.